2011
DOI: 10.1111/j.1742-4658.2011.08140.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of toxicity of Clostridium perfringens epsilon toxin

Abstract: Clostridium perfringensε‐toxin is produced by toxinotypes B and D strains. The toxin is the aetiological agent of dysentery in newborn lambs but is also associated with enteritis and enterotoxaemia in goats, calves and foals. It is considered to be a potential biowarfare or bioterrorism agent by the US Government Centers for Disease Control and Prevention. The relatively inactive 32.9 kDa prototoxin is converted to active mature toxin by proteolytic cleavage, either by digestive proteases of the host, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 90 publications
(151 reference statements)
0
96
0
Order By: Relevance
“…Previous studies suggested that in MDCK cells exposed to ETX, a large membrane complex formed on the cell surface [38], leading to pore formation, efflux of K + , influx of Na + , Ca 2+ , and Cl − ions, and finally rapid cell death [3,11]. In ETX-treated RBCs, we observed an increase of intracellular Ca 2+ , which could be mostly inhibited by an antagonist of P2 receptors (S6 Fig).…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Previous studies suggested that in MDCK cells exposed to ETX, a large membrane complex formed on the cell surface [38], leading to pore formation, efflux of K + , influx of Na + , Ca 2+ , and Cl − ions, and finally rapid cell death [3,11]. In ETX-treated RBCs, we observed an increase of intracellular Ca 2+ , which could be mostly inhibited by an antagonist of P2 receptors (S6 Fig).…”
Section: Discussionmentioning
confidence: 53%
“…C. perfringens epsilon toxin (ETX) is mainly produced by C. perfringens types B and D [2]. The toxin is the aetiological agent of dysentery in newborn lambs but is also associated with enteritis and enterotoxaemia in goats, calves and foals [3]. ETX is the third most lethal of all clostridial toxins, ranking behind only the Clostridium botulinum and Clostridium tetani neurotoxins [4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations